2022
DOI: 10.1177/03331024221103811
|View full text |Cite
|
Sign up to set email alerts
|

The monoclonal CGRP-receptor blocking antibody erenumab has different effects on brainstem and cortical sensory-evoked responses

Abstract: Objectives It is unclear whether the electrophysiological effects of erenumab, a monoclonal antibody against the calcitonin gene-related peptide receptor, occur only at the periphery of the trigeminal system or centrally and at the cortical level. Methods We prospectively enrolled 20 patients with migraine who had failed at least two preventative treatments. We measured the nociceptive blink reflex and non-noxious somatosensory evoked potentials in all participants. The area under the curve and habituation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…In addition, we found that habituation of nBR and nTCR that was deficient at baseline, normalizes after BoNT-A. This suggests that, by decreasing the afferent firing, BoNT-A could enhance the inhibitory antinociceptive activity of the brainstem-STN on sustained nociceptive stimulations, which in turn would be responsible for the progressive reduction in response magnitude of the trigeminocervical system [ 27 ]. The fact that the BoNT-A injections normalize contralateral, but not ipsilateral, nBR habituation could be related to the previous observation of an inverse relationship between initial (1st block) amplitude and the degree of late habituation [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we found that habituation of nBR and nTCR that was deficient at baseline, normalizes after BoNT-A. This suggests that, by decreasing the afferent firing, BoNT-A could enhance the inhibitory antinociceptive activity of the brainstem-STN on sustained nociceptive stimulations, which in turn would be responsible for the progressive reduction in response magnitude of the trigeminocervical system [ 27 ]. The fact that the BoNT-A injections normalize contralateral, but not ipsilateral, nBR habituation could be related to the previous observation of an inverse relationship between initial (1st block) amplitude and the degree of late habituation [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…For these purposes, we studied, in a group of chronic drug-resistant migraine patients, the trigeminal and extratrigeminal system at different levels through the use of electrophysiological techniques before and 1 and 3 months after a single injection session with BoNTA, according to the PREEMPT protocol [ 26 ]. Specifically, we electrically stimulated the supraorbital region and simultaneously recorded the nociceptive blink reflex, which reflects the activity of the caudal trigeminal nucleus [ 27 ]; the trigemino-cervical reflex, which studies the integrity of cervical motoneurones related to the trigeminal system [ 28 ]; and the pain-related cortical evoked potential, which reveals the activity of the cingulate area [ 29 ]. In addition, for each patient, we acquired somatosensory cortical evoked potentials from median nerve stimulation at the wrist, a way to assess the integrity of the non-pain-related somatosensory lemniscal system [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both studies suggest the importance of a central pain generator in the pathophysiology of CH. Cumulative evidence from functional imaging studies (109,110) and neurophysiological studies (111,112) suggests that there is a central effect of CGRP-mAbs, albeit probably secondary to peripheral drug modulation. Some even suggest a differential central effect of CGRP-mAbs between responders and non-responders (109,110).…”
Section: Anti-calcitonin Gene-related Peptide Therapymentioning
confidence: 99%
“…De forma similar, un estudio evaluó el blink reflex nociceptivo antes y tras tres meses de tratamiento con anti-PRGC en 22 pacientes con migraña episódica, demostrando una normalización significativa de los valores de R2 26 . Estos hallazgos se replicaron también con erenumab en un grupo de 20 pacientes, en los que además de una reducción del blink reflex a los 28 días, se observó una normalización de los potenciales evocados somatosensoriales a los 56 días, suponiendo que el efecto central del fármaco actúa primero a nivel del tronco y posteriormente a nivel cortical 27 . Ambos trabajos sugieren, por tanto, que el tratamiento induce modificaciones funcionales centrales del procesamiento nociceptivo.…”
Section: Impacto De Los Tratamientos Con Anticuerpos Anti-prgc En La ...unclassified